Pemanfaatan Sistem Informasi Gaji (SIMGAJI) dalam Perhitungan Tunjangan Keluarga Aparatur Sipil Negara di Kabupaten Sikka - Maria Donaines Bevinuresi; Antonius Philipus Kurniawan; Cicilia Ayu Wulandari Nuwa (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
This research focuses on the utilization of SIMGAJI in calculating family allowances where we can see whether the utilization is effective and efficient or not in using SIMGAJI so that it can be seen by calculating family allowances. To identify problems, this research uses qualitative research. Data collection techniques using interview techniques, observation, document studies. It can be concluded that the utilization of the Salary Information System (SIMGAJI) by PT. Taspen (Persero) for the calculation of family allowances for State Civil Apparatus (ASN) in Sikka Regency provides several significant advantages. SIMGAJI simplifies the management of salary and allowance data, ensures transparency, and improves the efficiency and accuracy of calculations. This makes the financial administration process simpler and more structured, and reduces the possibility of errors in the calculation of family allowances.